Can We Better Constrain the Timing of GNAIW/UNADW Variability in the Western Equatorial Atlantic and Its Relationship to Climate Change During the Last Deglaciation?. Issue 8 (10th August 2021) - Guilderson, Thomas P.; Allen, Katherine; Landers, Jordan P.; Ettwein, Virginia J.; Cook, Mea S.
Abstract: We have revisited the well‐trod VM28‐122 core retrieved from the deep Colombian Basin, which includes sediments that reflect modern Upper North Atlantic Deep Water and extends through the last deglaciation into the last glacial period when the site was bathed in Glacial North Atlantic Intermediate Water. Here, we leverage the nearby Cariaco Basin's surface water radiocarbon reconstruction (reservoir age, and Δ R ) on the IntCal20 timescale to recast the period of the last deglaciation with a newly constrained age model. Based on the revised age model, we observe that the multimillennial decrease in benthic δ 13 C and B/Ca (which record δ 13 C of dissolved inorganic carbon and Δ[CO3 −2 ], respectively) began at 18, 100 ± 240 (95% CI) calibrated years BP, synchronous with Termination 1, as identified by changes in the Antarctic Ice Sheet composite and by the onset of rapid glacier recession in the Southern Hemisphere (Denton et al., 2010, https://doi.org/10.1126/science.1184119 ; Denton et al., 2021, https://10.1016/j.quascirev.2020.106771 ). The beginning of the decrease in benthic δ 18 O is concurrent with the changes in carbon chemistry or at most, a few hundred years later. It is no later than 17, 700 ± 300 (95% CI) yrs BP in our record, at the putative start of Heinrich Stadial 1. With sufficient data density (more than 2–3 control points per kyr) and an independent record of past surface water radiocarbon variations, it is possible to achieve late glacial and deglacial chronologies with fidelities similar to those of ice cores. Doing so in more oceanographic locations should shed light more broadly on the mechanisms instrumental to abrupt climate change. Key Points: Early last deglaciation oceanographic changes in the Caribbean were synchronous with abrupt climate change in the Southern Hemisphere Reorganization of Glacial North Atlantic Intermediate inferred from changes in benthic δ 13 C and (CO3 −2 ) of the deep Caribbean Sea occurred at 18, 100 ± 240 cal years BP The geochronological approach exhibited in this study could be used as a template by the paleocommunities